EFL Teachers’ Best Practices of Merdeka Curriculum Implementation in Batam Senior High Schools: Challenges and Opportunities - Zaki, Leil Badrah; Wiwit, Jennifer; Marsevani, Maya; Pratiwi, Theodesia Lady (Journal of Languages and Language Teaching, 2025)
The Merdeka Curriculum was introduced to address the need for a more flexible and responsive education system, which is crucial in a diverse country like Indonesia. Educational challenges vary significantly between urban and rural areas and public and private schools. This study investigates the factors that hinder the implementation of the Merdeka Curriculum and examines how English teachers apply it in senior high schools located in inland and hinterland areas of the Riau Islands region.. The methodology used a mixed-method approach. The research involved 30 English teachers—23 from island schools and 7 from hinterland schools. Data were gathered through questionnaires and semi-structured interviews, with 5 teachers providing in-depth insights during interviews. The results reveal significant gaps in implementation, particularly among hinterland teachers, where 42.9% reported limited adaptability. The finding shows that each teacher faces unique challenges, which include: 1) administrative costs, 2) adjustments to new curricular components, and 3) a lack of government support, all of which hinder successful integration of the curriculum. To successfully implement the Merdeka curriculum, the following are essential: 1) involvement and support from all parties, 2) comprehensive teacher training, and 3) teachers' readiness. This study emphasizes that the successful implementation of the Merdeka Curriculum depends on the active participation of every school, ensuring that there is readiness, support, and adaptation to the new educational framework.